التفويض الإداري في النظام القانوني الجزائري - منيرة بوضياف; مبروكة قطار (My University, 2016)
Summary: Today's administrative delegation is an imperative that has been created to expand the activity of the State and to increase the number of officials in the administration. It was emphasized by the nature of the organization in the administrative organ. It aims to improve the functioning of central administrative affairs and decentralization. The delegation requires the transfer of certain powers from the administrative head to his subordinates and thus Authorization has some types, including the delegation of competence and the authorization of signature, as well as types in terms of the form of the source, and the authorization process for its establishment requires the existence of elements of the authorization persons: President and subordinate delegated to him, as well as delegated competencies, As a result of the delegation process, the administrative delegation is subject to special provisions that distinguish it from other similar regulations, A set of conditions must be met, whether objective or formal, as we have seen before, so that the delegation is correct. What is forgotten is the paramount importance of administrative delegation, whether for the administrative organ, including the absence of the administrative leader and others or for the chief administrative officer, such as relieving the burden of him, so that he is devoted to the most important issues and leaving ordinary matters to his subordinates... etc. It is also important for the administrative head by developing his spirit of innovation and initiative. Satisfying the psychological needs of him by strengthening his relationship with his administrative head by cultivating confidence in himself through the method of delegation.... etc.